'Give me my pathway!': multinational migration, transnational skills regimes and migrant subjectification. (9th June 2020) - COLLINS, FRANCIS L.
Abstract: In this article, I address the interplay between migration regimes and migrant subjectivities in stepwise multinational migration through a comparative analysis of biographical interviews with migrants in the healthcare and dairy farm work sectors in New Zealand. In both sectors, migrants' trajectories involve movements from Asia to locations in the Middle East, North Africa or Japan before arrival in New Zealand, and in some cases plans for onward migration. The analysis of these migration patterns and the narratives of migrants, reveal an emergent transnational skills regime that involves connected but uncoordinated systems of skills recognition; negotiating this regime occurs through increased attunement to migration on the part of multinational migrants, as well as adaptation to the expectations of authorities and employers. I conclude the article by suggesting that while multinational migration involves new opportunities for people on the move it also entails greater entanglement in the unequal conditioning of transnational migration.